UU Pesantren wujud Demokratisasi Pendidikan Islam - Moh. Ali Masud (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2020)
The birth of the Islamic Boarding School is an extraordinary gift from God. Why not, pesantren have now placed themselves on a par with formal education. As we know that previously pesantren were considered to be of poor quality educational institutions, pesantren graduates had difficulty competing with formal institution graduates, even though these had not been proven to be true. The Islamic Boarding School is a manifestation of democratization of Islamic Education. Islamic educational institutions are increasingly believed to be able to compete with formal education by the general public. As an effort to develop, pesantren must make new breakthroughs in order to adjust the demands of the times without losing the old culture.